Drawing lessons for the creation of regional governments under a federal setup : case study on the Autonomous Region in Muslim Mindanao - The Congressional Policy and Budget Research Department (Quezon City : The Congressional Policy and Budget Research Department, 2017)
printed from the website of the Institute of Autonomy and Governance
Keywords: Autonomous Region in Muslim Mindanao (ARMM).; Constitutional law -- Philippines; Federal government -- Philippines; Local government -- Philippines -- Autonomous Region in Muslim Mindanao; Muslim -- Legal status, laws, etc. -- Philippines -- Autonomous Region in Muslim Mindanao